Energy availability and Relative Energy Deficiency in Sport (REDs) among Icelandic athletes - Varðardóttir, B. (University of Iceland, 2024)
Background: Relative Energy Deficiency in Sport (REDs) describes various health and performance complications of problematic low energy availability (LEA). Sex and sport-specific aetiology and risk factors, in addition to the degree of LEA resulting in REDs remain to be adequately described.